COMPARISON OF THE EFFICIENCY OF VARIOUS GAS INDUSTRY SCHEMES BY THE MATHEMATICAL MODELING - M. Kuternin (Вестник университета)
A quantitative comparison of the optimal characteristics of two schemes of construction of the gas industry of the national economy, using mathematical modeling – a scheme with full vertical integration of the industry and a scheme with a vertical division of the industry into a competitive gas production sector and a gas transportation system, which is a natural monopoly сore of the industry – has been carried out. It has been established, that allocation of the competitive making sector can give small increase in total amount of gas production and the same reduction of price for the end user, but can lead to decrease in investments into the development of the industry. It has been concluded, that the decision on a form of existence of the industry demands joint consideration both economic and political aspects of the problem.